PENGARUH PEMBERIAN KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN LAPANGAN PT. DWIKARYA MANDIRI EKSPRESSINDO - Rahma Iklila Siswanto; Hanuna Shafariah (JAMBIS : Jurnal Administrasi Bisnis, 2023)
Compensation, a good working environment and motivation are basically the rights of employees and it is the role of the company to support the participation of its employees in achieving the goals that have been set so as to improve employee performance. The purpose of the study to determine the effect of compensation and work environment has a positive effect on employee performance at PT. Dwikarya Mandiri Ekspressindo. This research is Quantitative that is a method of producing knowledge that uses data in the form of valid numbers such as tools to analyze the description of what you want to know. According to Sugiyono (2017: 81) the sample is part of the population that is the basis of information in research, where the population is part of the number of characters owned by the population. Therefore, because the population as much as 45 people then for sampling techniques using saturated sempel method. From the results of research obtained compensation does not affect the importance of employee performance terhdap, where the Number t amount received is 1. 067 and the number T chart is 2. 017 (df42). the value of T is smaller than the value of T and the significance of T is greater than the value of alpha (0. 292 0. 05), as well as lingkugan important influence on employee performance. This is indicated by the Number t the amount received is 3. 958 and T Chart Number 2. 017 (df42) is less significant than alpha (0. 000 0. 05). That way, it can be concluded that there are positive and important consequences for elastic areas of activity to elastic employee performance. Elastic compensation (X1) and the area of activity (X2) in a way together have an important impact on the performance of employees of PT. Dwikarya Mandiri Ekspressindo. As shown in Figure f (18). 860) F chart (3. 220), which means compensation as well as the environment of activities in a way that together have a role in influencing the performance of employees of PT. Dwikarya Mandiri Ekspressindo.